Apport des techniques géo-spatiales pour la caractérisation de la qualité des eaux souterraines des oasis de la vallée du Draa : cas de la nappe de Fezouata - Cherkaoui H.D.; Moussadek R.; Sahbi H. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
The Middle Draa, narrow depression between the Saghro and the Sahara, constitutes a discontinuous hydraulic surface entirely dependent on Draa whose very irregular mode was regularized by the Mansour Dahbi Dam. Since its operation, this dam could improve the availabilities out of water in the Middle Draa, following the mobilization of surface waters and consequently increase the surfaces annually cultivable, which modified the mode of the subjacent. Also, through this paper, we propose to show the contribution of the Geographical Information System in order to contribute to a brought up to date hydro-geologic synthesis of these ground waters particularly that of Fezouata and to define its principal potentialities.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)